The Impact of Health Insurance on the Access to Health Care and Financial Protection in Rural Developing Countries : The Example of Senegal - Jutting, Johannes Paul (World Bank, Washington, DC, 2013)
Community-based health insurance schemes are becoming increasingly recognized as an instrument to finance health care in developing countries. Taking the example of "les mutuelles de santes" (mutual health organization) in rural Senegal this paper analyzes whether or not members in a mutual health insurance scheme have better access to health care than nonmembers. A binary probit model is estimated for the determinants of participation in a mutual and a logit/log linear model is used to measure the impact on health care utilization and financial protection. The results show that, while the health insurance schemes reach otherwise excluded people, the very poorest in the communities are not covered. Regarding the impact on the access to health care, members have a higher probability of using hospitalization services than nonmembers and pay substantially less when they need care. Given the results of this study, community financing schemes have the potential to improve the risk-management capacity of rural households. To reduce identified limitations of the schemes, an enlargement of the risk pool and a scaling up or linking of the schemes is, however, a prerequisite. Appropriate instruments to be further tested should include reinsurance policies, subsidies for the poorest and developing linkages to the private sector via the promotion of group insurance policies. All these instruments call for a stronger role of public health policy.